(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2009)
Supraventricular tachycardia, though not very common may develop in any patient under spinal anaesthesia. A 50 years old lady admitted at square hospital through the emergency unit with left loin pain and fever with chill. She was already diagnosed as a case of left ureteric stone and was scheduled for Ureteorenoscopic Intracorporeal Pneumatic Lithotripsy (URS-ICPL) under spinal anaesthesia. During anaesthesia, she developed supraventricular tachycardia of unknown origin. Ultrashort-acting (3-blocker was given slowly. As there was no improvement, intravenous propranolol was given slowly, which resulted in a conversion to sinus rhythm. This paper discussed methods of cardio version for patients with supraventricular tachycardia in such clinical settings. Key words: Spinal anaesthesia, SVT. Journal of BSA, Vol. 21, No. 1, January 2008 56-58